The Virtual Communities and Education - Ana Maria Arişanu LACULEANU (Informatică economică, 2006)
The progress made in the information and communication technology builds new communication and connection opportunities of the citizens and organizations leading to an important change of the citizen's behavior and of the functioning way of the organizations. The intelligence, as the only lasting active of a organization, is made up of individual and collective knowledge. As a matter of fact, the citizens feel more often the need of information and communication, the organizations are trying to rebuild the information so that the access to the useful information to become as easy as possible. The virtual communities appeared and are developing as a result of rising the trust grade in the major role that the Internet plays in the informational society. The educational portals, weblogs and the group software infrastructure are becoming necessary instruments in the present educational systems.